Longitudinal EpiTrack assessment of executive functions following vagus nerve stimulation therapy in patients with drug‐resistant epilepsy - Niina Lähde; Pabitra Basnyat; Jani Raitanen; Kai Lehtimäki; Eija Rosti‐Otajärvi; Jukka Peltola (Epilepsia Open, 2024)
Abstract Objective To investigate executive functions and attention with repeated EpiTrack evaluations in a group of DR patients with drug‐resistant epilepsy (DRE) receiving vagus nerve stimulation (VNS) during a follow‐up duration of up to 5 years. Methods The study involved 33 patients with DRE who were assessed with EpiTrack as a part of the clinical VNS protocol. Evaluations were scheduled prior to VNS implantation and then at 6 months, 12 months, and yearly thereafter. However, the COVID‐19 pandemic disrupted follow‐up. Therefore, changes in EpiTrack total scores over time were analyzed using a linear mixed‐effects (LMEs) model to compensate for the variation in follow‐up duration when predicting EpiTrack total score changes over 5 years. Results The median follow‐up time was 29 months. During each month, the EpiTrack total score was predicted to increase by 0.07 units (95% confidence interval [CI]: 0.01–0.12, P = 0.02), corresponding to a change from a baseline score of 27.3 (severe impairment) to a score of 28.9 (mild impairment) at 2 years and a score of 31.5 (almost normal) at 5 years. In the group of patients with psychiatric comorbidities, the EpiTrack total score increased by 0.14 units per month (P = 0.003), which was 3.5‐fold higher than the increase of patients without psychiatric comorbidities. For the patients taking 1–2 antiseizure medications (ASMs), the EpiTrack total score increased by 0.11 units per month (P = 0.005), which was almost quadruple the rate of patients taking 3–4 ASMs. Significance Based on EpiTrack total scores, the LME model predicted a four‐point improvement in executive functions among patients with DRE at 5 years after the initiation of VNS, representing a clinically meaningful change. DRE patients with comorbid depression seemed to experience the most cognitive benefits. In addition, better cognitive outcomes were achieved if the patient took less than three ASMs. Plain Language Summary Executive functions and attention may improve during vagus nerve stimulation therapy in patients with drug‐resistant epilepsy. Epilepsy patients who have depression or use fewer than three antiseizure medications are likely to benefit cognitively more from the treatment.